Exploring Prison Educators’ Perspectives on What Strategies They Deem as Being Effective When Supporting Prisoners as Learners - McDonagh, Aoife (TARA, 2021)
This article examines the prison education system in Ireland, in particular, prison educators’ perspectives on prison education, what teaching strategies they use and deem effective when supporting prisoners as learners
Journal article
Keywords: Prison; Andragogy; Educators Perspectives; Teaching and Learning; Prior Knowledge; Prisoners--Education; Adult education educators